Gene mutations and environmental factors that influence the onset of autism (Research, Society and Development, 2025)
Introduction: Autism Spectrum Disorder (ASD), also known as autism, is a multifactorial neurodevelopmental disorder, whose causes are not fully understood yet. Recent studies indicate that genetic and epigenetic factors, associated with environmental conditions, may play a significant role in the etiology of the disorder. Objective: This study aimed to identify and analyze the main gene mutations and environmental factors that influence the development of ASD. Methodology: A literature review was carried out using scientific databases, focusing on publications from the last ten years. Results and Discussion: The results indicate that genes such as CHD8, SHANK3, MECP2 and SYNGAP1, among others, are frequently associated with autism, while factors such as gestational stress, infections, pollution and use of medications during pregnancy can trigger epigenetic changes that affect the neurodevelopment. Conclusion: It is concluded that the interaction between genetic alterations and environmental exposures may be decisive for the development of ASD, highlighting the importance of integrative studies in the search for prevention strategies, early diagnosis and more effective therapeutic interventions.